Preliminary study on the characterization of forward osmosis hollow fiber membranes - Ng, Yen Ting. (2011)
Forward osmosis (FO) has received intensive studies recently for its potential application in water production and treatment processes. Many of the past researches paid great emphasis in optimizing the commonly used asymmetric composite FO membrane structure to achieve high water flux and solute rejection. An asymmetric composite FO membrane generally consists of a dense rejection layer with a porous support layer underneath. The porous support layer is an open-structure that is incapable of preventing foulants from penetrating into its pores; hence unfavorable membrane internal fouling maybe resulted.In this work, the outer surfaces of two different types of porous substrates in an asymmetric composite polyethersulfone (PES) membrane; #A-Substrate and #B-Substrate were made denser to effectively prevent membrane internal fouling. The substrates are modified via two outer surface modification methods namely layer-by-layer alternating deposition of polyelectrolytes and plasma treatment